Age-linked Groups in the Early Iron Age nomadic societies (preliminary results) - Berseneva Natalia A. (Поволжская археология)
Age-linked symbolism was often an important part of the burial ritual. The study aims to reconstruct age-linked social groups in the nomadic societies in the Southern Urals during the Early Iron Age (late 5th – 3rd centuries BC). The source base consisted of 23 published and partially published burial grounds and separate barrows of the Early Sarmatian period. The sample consisted of 183 individuals (141 females, 142 males) with gender and age (in years) identification. For analysis, only those burials were used where the individual belonging of the inventory did not cause doubts. Analysis of the sample showed that the age of the adult deceased (young, mature, elderly) was not determinant for the choice of weapons as accompaniments. There is a tendency for the amount of decoration to decrease with age аmong female burials. We can conclude that the peak of social activity lasted longer for men than for women. The correlation of age groups with other types of artifacts (cult objects, household items, horse harness or certain types of weapons/decorations), as well as with markers of high social status (prestigious things, labor-intensive structures) may be one of the further directions of research.